4. Satellite Remote Sensing Application in Assessing Soil Erosion of a Watershed - Chakraborty, Debashis; Dutta, Dibyendu; Chandrsaekharan, H. (Journal of Soil and Water Conservation, 2022)
The application of satellite remote sensing data in assessing the potential soil losses from the Birantiya Kalan watershed in Pali district of western Rajasthan is discussed in this paper. The data were for 1988 and 1996, respectively, the pre- and post- treatment year. The treatments were given under the National Watershed Development Project for Rainfed Areas (NWDPRA). The Universal Soil Loss Equation (USLE) was applied with ARC/INFO-GIS to predict the soil erosion status of the watershed. The crop factor in the USLE was derived from satellite data. Though the erosion potential was found to be below the permissible limit for both the years, it was higher in 1996. Accordingly, the need of periodic monitoring for assessing the management alternatives is felt. The GRID-based surface modeling for soil erosion with satellite remote sensing data as major input was found to be rational and realistic in predicting and monitoring of runoff and soil erosion of this remotely located watershed, where it is difficult to get actual field observations.